In search of bachelorettes: Observations of male Leptonycteris yerbabuenae with dorsal patches across its range - Laverty, Theresa M.; Stoner, Kathryn E. (THERYA, 2022)
The lesser long-nosed bat (Leptonycteris yerbabuenae) is a partially migratory, nectarivorous species that exhibits reproductive asynchrony across its range. Both migratory and resident populations of sexually active males of L. yerbabuenae may form an odoriferous dorsal patch during their mating season. This is created by smearing saliva, urogenital fluids, and anal secretions over the interscapular dorsal region with their feet. Dorsal patches are believed to influence female mate choice. We synthesized the sightings of male dorsal patches across the species’ range, including gathering new observations of male L. yerbabuenae with dorsal patches captured at the northern extent of their range and citing previously unreported observations that we obtained by contacting other researchers. We also conducted a literature review to include all previously documented records of male L. yerbabuenae presenting dorsal patches. We document the first observations of male L. yerbabuenae with dorsal patches in the southwestern United States. In the Big Hatchet Mountains in New Mexico, we captured 1 male with a developed dorsal patch (i. e., bare dorsal skin with sticky fur) on 25 July 2019 and two others on the night of 13 August 2019. New observations of males with developed dorsal patches were obtained from Hilltop Mine in Arizona (June 2006 or 2007) and at a hummingbird feeder at a residence near the Hilltop Mine (July 2013). A male with a recovering dorsal patch (i. e., bare dorsal skin with regenerating fur) was also captured in a roost near Patagonia, Arizona, in late August 2008 and at a hummingbird feeder at a residence near Silver City, New Mexico (September 2021). All previously published records of males with dorsal patches occurred in roosts in Mexico during known mating seasons. These new observations suggest that L. yerbabuenae may breed in New Mexico and Arizona between June and August, but follow-up studies are needed to confirm this behavior. Much of the reproductive biology of this important pollinator remains unknown. Therefore, identifying regions where males present dorsal patches may not only assist in locating and protecting mating roosts, but would also further our understanding of the population ecology of this migratory species.